Characterization of CsI(Tl) and LYSO(Ce) scintillator detectors by measurements and Monte Carlo simulations. (December 2019) - Mouhti, I.; Elanique, A.; Messous, M.Y.; Benahmed, A.; McFee, J.E.; Elgoub, Y.; Griffith, P.
Abstract: In this study, we investigated the performance of two cuboid scintillation detectors: thallium-activated cesium iodide [CsI(Tl)] and cerium-doped lutetium yttrium orthosilicate [LYSO(Ce)]. The CsI and LYSO crystals were 5 mm thick with an active area of 10 mm × 10 mm. The LYSO scintillator is characterized by its high stopping power and non-hygroscopicity (neither packaging nor light guide are required). Nevertheless, the main disadvantages of LYSO detectors are a lower light output (32 photons/keV) and an intrinsic radioactivity caused by the β − decay of 176 Lu (half-life 3.78 × 10 10 years). In contrast, CsI crystals present a relatively high light output (54 photons/keV) allowing better energy resolution; however, the drawback of a CsI detector is low detection efficiency. First, we measured the photon detection efficiency of each scintillator in the photon energy range of 60–1332 keV using radioactive sources. Second, we computed detector efficiencies using the Monte Carlo codes MCNP and Geant4. A comparison between simulated and measured efficiencies showed a good agreement. This comparison confirmed the validity of the mathematical models developed for the two scintillation detectors CsI(Tl) and LYSO(Ce) under investigation. Highlights: CsI(Tl) and LYSO(Ce) scintillator detectors (10 × 10 × 5 mm) characterized experimentally. Energy resolution and detection efficiency measured in photon energy range 60–1332 keV. Detector efficiencies computed using Monte Carlo codes MCNPX and Geant4. Mathematical models developed for the CsI(Tl) and LYSO(Ce) detectors validated.